Proposed Marketing Communication Strategy To Increase Consumer Brand Awareness And Purchase Intention (Case Study: Yogya Online) (The Indonesian Journal of Business Administration, 2021)
The development of technology information influences the shift in behavior, economic, and business. One of the most visible changes is the shift in business method. These changes showed by the rapid increase of e-commerce. Yogya Group took this opportunity to establish its own e-commerce, using the name of Yogya Online. This research aimed to assist Yogya Online in increasing brand awareness and consumers’ purchase intention by identifying which factors influence consumers and proposing business solution based on these factors. There are two factors that are being examined in relation to brand awareness. This factor are marketing communication and website characteristic. On the other hand, there are four factors related to purchase intention that are studied. These factors are brand awareness, equity driver, marketing communication, and website characteristic. The result showed that marketing communication and website characteristic factors are significantly related with brand awareness. Brand awareness has significant positive influence toward equity driver. Brand awareness, marketing communication, and website characteristic factors are significantly related with purchase intention. However, equity driver factor is insignificantly related with purchase intention. Among these factors, website characteristic has the strongest relation with purchase intention. Keywords: Brand Awareness, Purchase Intention, Online Grocery Shopping